PENGARUH IMPLEMENTASI RELATIONSHIP MARKETING TERHADAP TINGKAT KEPUASAN PASIEN DI RUMAH SAKIT UMUM “YAKKSI” GEMOLONG SRAGEN - Budhi Poniman (BHIRAWA, 2013)
This study aimed to determine the effect of relationship marketing strategy that consists of understanding the expectation of patients, formed a partnership with the patients, employees empowerment and total quality management on the level of satisfaction of patients hospitalized "YAKKSI" Gemolong Sragen. Based on the results of data analysis and hypothesis testing summarized as follows: The multiple Linear Regression Test could be concluded that understanding the expectation of patients, formed a partnership with the patients, employees empowerment and total quality management have a positive effect on the dependent variable patient hospital "YAKKSI" Gemolong Sragen in the rate of satisfaction. F-test Result was jointly independent variables have positive effect on patient satisfaction in "YAKKSI" hospital at Gemolong Sragen. T-test could be concluded that the independent variable had a positive and significant effect on the dependent variable. R2 adjusted shew of 60.6%, which meant that variables understanding the expectations of the patients, the patient's cooperation, employees’ empowerment and total quality management effect on patient satisfaction at "YAKKSI" hospital at Gemolong Sragen of 60.6%. Keyword :relationship, marketing, satisfaction